The Effectiveness of Problem Based Learning Model to Improve Students' English Learning Outcomes at Ban Klongrua School, Thailand - Nurlaelli, Mia Sofi; Fitriyani, Yani; Hadiana, Oman; Manan, Nanan Abdul; Hermawan, Hermawan (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research aims to determine the effectiveness of the Problem Based Learning model on English learning outcomes for Class IV Ban Khlongrua School Krabi, Southern Thailand. This type of research is pre-experimental research in the form of one group pretest posttest, namely an experiment. The experimental research unit was fourth grade students at Ban Khlongrua School Krabi, Southern Thailand. The results of descriptive statistical analysis of English learning outcomes using the Problem Based Learning Model show better results than before using the Problem Based Learning Model. The results of inferential statistical analysis using the t-test formula show that the calculated t value obtained is 2.79 with a frequency of dk = 10-1 = 9. At the 5% significance level, the t table value = 0.45. So, ct-ount > ttable or 2.79 > 0.45. This proves that the application of the Problem Based Learning model in English learning has an influence so that it can be said to be more effective than before the use of the Problem Based Learning Learning Model.